Cerebellar involvement in olfaction: An fMRI Study. Issue 3 (30th March 2021) - Zhang, Zi‐hao; Liu, Xiao; Jing, Bin; Hu, Bao‐min; Ai, Zheng; Xing, Bo‐kai; Jiang, Tao; Peng, Peng
ABSTRACT: Background and Purpose: The role of the cerebellum in olfactory function is not fully understood. In this study, we tried to combine resting state and task functional MRI (fMRI) to improve the understanding of the cerebellum during olfactory processing. Methods: A resting state and a block paradigm of olfactory stimulation fMRI were scanned in 50 subjects. The olfactory stimuli, including phenylethyl alcohol and isovaleric acid, were alternately delivered to the subject using a custom‐built olfactometer through air flow. The cerebellar activations elicited by isovaleric acid were subsequently used in the seed‐based resting‐state functional connectivity study. Results: Phenylethyl alcohol did not induce any cerebellum activation, while isovaleric acid with a more unpleasant smell elicited significant cerebellum activations, primarily in the bilateral posterior lateral hemispheres (bilateral lobule crus I and right lobule VI). Seed‐based functional connectivity analysis revealed significant within‐cerebellum and corticocerebellar connections. Conclusions: The results imply that the cerebellum is probably involved in olfactory‐related responses caused by unpleasant odor but does not directly participate in olfactory perception. Our results may further improve the understanding of the cerebellum in olfactory function.